The cultures of families. Parenting and participation in early childhood educational services in Reggio Emilia - Manuela Tassan; Daniela Lanzi (University of Bologna, 2022)
Starting from a concrete collaborative experience, the article aims to discuss the role, as well as the multiple declinations, that collaboration between pedagogical and anthropological knowledge can assume in the promotion of self-reflective practices in the field of childhood services for children in the 0-6 age group. The focus will be, in particular, on The culture of families, a project and training process, started in 2019 and still ongoing, which has involved a group of teachers of the Municipality of Reggio Emilia's infant-toddler centres and preschools. The initiative was born with the aim of questioning the changes taking place in contemporary families in order to understand how to encourage participation in educational services. The pandemic crisis, however, has transformed the project also into a fundamental opportunity for collective reworking of the challenges posed by this particular historical moment. This contribution will analyse the project's strategy and the theoretical suggestions opened up by this experience, which has been profitably interwoven with the participation of some teachers in training and research activities in the anthropological field.